A phenomenological study of parents with adolescents abusing nyaope in Mokopane, South Africa - Ramulwela, Takalani Vincent (My University, 2024)
Parenting an adolescent who abuses nyaope drug is a difficult task fraught with several difficulties. The present study explored the lived experiences of parents with adolescents who abuse nyaope with the aim of developing a research informed Help- Seeking Model around the rural areas of Mokopane in the Limpopo Province, South Africa. Parents’ subjective experiences were gathered through the qualitative approach using the Hermeneutic phenomenological design. Data were analysed using the Interpretative Phenomenological Analysis (IPA). The study found nyaope to be a potent yet easily accessible drug of choice for teenagers in rural and township settings. Nyaope abuse risk factors were isolated and ranged from being of a psychosocial and spiritual nature. The deleterious nature of the condition meant parents’ quality of life and well-being were compromised, including due to social stigma. Parents relied on religious, psychological, and social strategies for coping. It was discovered that several paths or trajectories, i.e., a combination of the medical, psychiatric, social-welfare, and spiritual services pathways, were necessary for the treatment of their affected youth. Based on the study findings, an adapted nyaope Help-Seeking Model is proposed for early identification and management of affected adolescents. The study also has several implications for clinical practice, further research, and policy development. It is concluded that nyaope abuse is a potent drug, which early identification of signs and symptoms indicative of use, is necessary towards sustainable interventions. Key in its management is addressing the risk as early as possible to lessen teenager vulnerability to the drug.
Thesis (Ph. D. (Psychology)) -- University of Limpopo, 2024
Keywords: Nyaope abuse; Parents; Help-seeking pathways; Drug abuse; Drugs of abuse -- Physiological effect; Teenagers; Parents of drug addicts